Evaluation of United States chiropractic professional subgroups: a survey of randomly sampled chiropractors - Jordan A. Gliedt; Stephen M. Perle; Aaron A. Puhl; Sarah Daehler; Michael J. Schneider; Joel Stevans (BMC, 2021)
Abstract Background Professional subgroups are common and may play a role in aiding professional maturity or impeding professional legitimization. The chiropractic profession in the United States has a long history of diverse intra-professional subgroups with varying ideologies and practice styles. To our knowledge, large-scale quantification of chiropractic professional subgroups in the United States has not been conducted. The purpose of this study was to quantify and describe the clinical practice beliefs and behaviors associated with United States chiropractic subgroups. Methods A 10% random sample of United States licensed chiropractors (n = 8975) was selected from all 50 state regulatory board lists and invited to participate in a survey. The survey consisted of a 7-item questionnaire; 6 items were associated with chiropractic ideological and practice characteristics and 1 item was related to the self-identified role of chiropractic in the healthcare system which was utilized as the dependent variable to identify chiropractic subgroups. Multinomial logistic regression with predictive margins was used to analyze which responses to the 6 ideology and practice characteristic items were predictive of chiropractic subgroups. Results A total of 3538 responses were collected (39.4% response rate). Respondents self-identified into three distinct subgroups based on the perceived role of the chiropractic profession in the greater healthcare system: 56.8% were spine/neuromusculoskeletal focused; 22.0% were primary care focused; and 21.2% were vertebral subluxation focused. Patterns of responses to the 6 ideologies and practice characteristic items were substantially different across the three professional subgroups. Conclusions Respondents self-identified into one of three distinct intra-professional subgroups. These subgroups can be differentiated along themes related to clinical practice beliefs and behaviors.